1977
DOI: 10.1111/j.1528-1157.1977.tb04989.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Etiological Factors in 1,785 Epileptic Subjects: Clinical‐Anamnestic Research

Abstract: SUMMARY This study utilizes ciinicai and anamnestic data concerning epileptic subjects (males and females) of ages ranging between 1 month and 21 years. These patients were treated in the Neurology Department of the University of Turin, during the following periods: 1948–1958, 1960–1964, 1970–1974. All possible etiologies of epilepsy were included in the study except those of genetic and tumoral origin. The clinic data, including 68,222 EEG recordings, were considered. An initial sample of 4,947 subjects, aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 5 publications
3
15
0
Order By: Relevance
“…From extrapolated information of the epilepsy studies it is found that HIE is related to a high percentage of epilepsies, however, these data vary from study to study ranging from 26% to 46%. 16,17,18,19,20,21,22,23,24 Active epilepsy starting at early age i.e., within 12 month of age if not well controlled and monitored, may affect the rate of developmental skills. Good seizure control probably had facilitated to grow out of the functional limitation among the control population.…”
Section: Discussionmentioning
confidence: 99%
“…From extrapolated information of the epilepsy studies it is found that HIE is related to a high percentage of epilepsies, however, these data vary from study to study ranging from 26% to 46%. 16,17,18,19,20,21,22,23,24 Active epilepsy starting at early age i.e., within 12 month of age if not well controlled and monitored, may affect the rate of developmental skills. Good seizure control probably had facilitated to grow out of the functional limitation among the control population.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of unprovoked seizures following bacterial meningitis occur within 5 years of the acute illness (de Graaf, 1974;Bergamini et al, 1977;Sell et al, 1977;Rantakallio et al, 1986;Annegers et al, 1988;Pomeroy et al, 1990;Chang et al, 2004). Unprovoked seizures following bacterial meningitis tend to be recurrent (Rosman et al, 1985;Annegers et al, 1988;Pomeroy et al, 1990).…”
Section: Seizure Semiology Course and Prognosismentioning
confidence: 99%
“…In the cohort of survivors of CNS infections in Olmsted County, Minnesota, the ratio of observed to expected (O:E) cases of unprovoked seizures was 6.9 (Annegers et al, 1988). In developed countries, 1-5% of incident cases of epilepsy are presumed to be due to prior CNS infections (de Graaf, 1974;Hauser & Kurland, 1975;Bergamini et al, 1977). The high incidence and prevalence of epilepsy in developing countries has partly been attributed to the endemic CNS infections (Commission on Tropical Diseases of the International League Against Epilepsy, 1994; Preux & Druet-Cabanac, 2005;Mac et al, 2007).…”
mentioning
confidence: 99%
“…Prior CNS infections account for 1-5% of epilepsy cases [45][46][47]. The incidence of postinfectious seizures is bimodal with the first peak occurring during childhood and the second peak in the elderly [48].…”
Section: Etiologymentioning
confidence: 99%